Te rakel norh romenes ko dives - Jean-Pierre Cavaillé (Lengas)
The article presents the observations and the analyzes of a Gadjo (non-Roma) eager to learn Sinto (Manush) dialect of the Romani language, still widely spoken today in France by individuals of all generations, but nevertheless in great difficulty and without any recognition. Reflection unfolds from the observation of the paradox constituted by a representation shared by the speakers of Manush as a major element of identity but also as a language reserved for the group, which must be kept away from the Gadjé, even though, in reality, the speakers show great spontaneity and benevolence in sharing the language, as soon as a Gadjo wishing to speak it presents itself.